CO2-assisted growth of millimeter-tall single-wall carbon nanotube arrays and its advantage against H2O for large-scale and uniform synthesis. (September 2018) - Sato, Toshihiro; Sugime, Hisashi; Noda, Suguru
Abstract: The CO2 -assisted chemical vapor deposition (CVD) is reported as a versatile method for millimeter-tall vertically-aligned single-wall carbon nanotube (VA-SWCNT) arrays when compared with the famous H2 O-assisted one. The mild oxidant CO2 enabled the VA-SWCNT growth with mostly equivalent structures and yield when it was added at a much higher concentration (0.3–1 vol%) than H2 O (50 ppmv). Furthermore, CO2 showed a clear advantage for the uniform growth when 18 substrates (10 × 10 mm 2 ) were loaded in one batch. The areal yield of VA-SWCNTs decreased drastically from 1.6 to 0.4 mg cm −2 for the first 4 substrates with 50 ppmv H2 O because of its depletion whereas it decreased more mildly from 1.6 to 0.8 mg cm −2 for the whole 18 substrates with 1.0 vol% CO2 . The gradual decrease in the SWCNT yield with 1.0 vol% CO2 was caused by the change in the carbon source depending on its position. The mixed feed of 0.30 vol% C2 H2 (being converted to SWCNTs gradually) and 3.0 vol% C2 H4 (yielding C2 H2 gradually) realizes the uniform growth of VA-SWCNTs for the whole 18 substrates. The CO2 -assisted CVD with optimized carbon feed is promising for the uniform growth of millimeter-tall SWCNTs in large areas. Graphical abstract: Image